Human Resource Development Strategy in Realizing Integrated and Globally Competitive Agrocomplexes - Sari, Winda (Journal of Agro Complex Development Society, 2025)
This study aims to analyze and formulate a strategy for developing human resources (HR) in realizing an integrated agrocomplex that is globally competitive. Using a mixed methods approach that integrates quantitative and qualitative methods, the study was conducted on 350 respondents representing various actors in the agrocomplex value chain in five agricultural center provinces in Indonesia. The results of the study indicate a gap in HR competency at various agrocomplex nodes, especially in the use of digital technology, post-harvest management, understanding international standards, and global marketing. Structural Equation Modeling (SEM) analysis confirmed the significant influence of individual characteristics (β = 0.437), institutional capacity (β = 0.385), access to technology and information (β = 0.324), and government policy support (β = 0.276) on HR competency, which in turn had a strong influence on agrocomplex competitiveness (β = 0.612). Qualitative findings revealed four main themes: generation gaps in agricultural management, limitations of the agricultural innovation support ecosystem, fragmentation of agricultural HR development programs, and the digital divide. Based on the Analytic Hierarchy Process (AHP), five priority strategies for human resource development were formulated, namely: (1) revitalization of agricultural vocational education and training; (2) strengthening the agricultural extension system based on digital technology; (3) development of penta-helix partnerships; (4) increasing the institutional capacity of farmers; and (5) developing incentives for young farmer cadres. This study concludes that human resource development is a fundamental prerequisite in realizing a globally competitive integrated agrocomplex, which requires a holistic approach and integration of interventions at the individual, institutional, and ecosystem levels. Policy recommendations are directed at the orchestration of cross-sectoral programs and strengthening synergies between stakeholders within the framework of agricultural transformation towards a modern agrocomplex.